MurA escape mutations uncouple peptidoglycan biosynthesis from PrkA signaling - Wamp, Sabrina; Rothe, Patricia; Stern, Daniel; Holland, Gudrun; Döhling, Janina; Halbedel, Sven (PLOS Pathogens, 2022)
Gram-positive bacteria are protected by a thick mesh of peptidoglycan (PG) completely engulfing their cells. This PG network is the main component of the bacterial cell wall, it provides rigidity and acts as foundation for the attachment of other surface molecules. Biosynthesis of PG consumes a high amount of cellular resources and therefore requires careful adjustments to environmental conditions. An important switch in the control of PG biosynthesis of Listeria monocytogenes, a Gram-positive pathogen with a high infection fatality rate, is the serine/threonine protein kinase PrkA. A key substrate of this kinase is the small cytosolic protein ReoM. We have shown previously that ReoM phosphorylation regulates PG formation through control of MurA stability. MurA catalyzes the first step in PG biosynthesis and the current model suggests that phosphorylated ReoM prevents MurA degradation by the ClpCP protease. In contrast, conditions leading to ReoM dephosphorylation stimulate MurA degradation. How ReoM controls degradation of MurA and potential other substrates is not understood. Also, the individual contribution of the 20 other known PrkA targets to PG biosynthesis regulation is unknown. We here present murA mutants which escape proteolytic degradation. The release of MurA from ClpCP-dependent proteolysis was able to activate PG biosynthesis and further enhanced the intrinsic cephalosporin resistance of L. monocytogenes. This latter effect required the RodA3/PBP B3 transglycosylase/transpeptidase pair. One murA escape mutation not only fully rescued an otherwise non-viable prkA mutant during growth in batch culture and inside macrophages but also overcompensated cephalosporin hypersensitivity. Our data collectively indicate that the main purpose of PrkA-mediated signaling in L. monocytogenes is control of MurA stability during standard laboratory growth conditions and intracellular growth in macrophages. These findings have important implications for the understanding of PG biosynthesis regulation and β-lactam resistance of L. monocytogenes and related Gram-positive bacteria.